Surgical treatments of superior semicircular canal dehiscence: A single‐centre experience in 63 cases. Issue 6 (24th November 2021) - Nieto, Pauline; Gallois, Yohan; Molinier, Charles‐Edouard; Deguine, Olivier; Marx, Mathieu
A bstract: Objective: Different procedures have been described to treat superior canal dehiscence. The present study aims to describe the results obtained with middle fossa approach, transmastoid approach, and round window reinforcement in a large series of patients. Methods and Design: In this single‐center retrospective study, we report the results of the procedures performed between 2006 and 2019 using the three main surgical approaches, middle fossa approach (MFA), transmastoid approach (TMA), and round window reinforcement (RWR). The outcome on cardinal cochlear and vestibular symptoms, audiometric results, and changes in cervical vestibular evoked myogenic potentials (cVEMPs) were analyzed. The patients were also interviewed 12 months to 13 years post‐treatment to establish their overall satisfaction following surgery. Results: Sixty‐three patients were divided into three groups: 42 MFA; 12 RWR; 9 TMA. Postsurgical control rates exceeded 80% for the majority of symptoms in the MFA and TMA groups, and ranged from 11.1% to 83.3% for the RWR group. Over 90% of MFA or TMA patients and 60% of the RWR cohort were satisfied overall with their treatment. Hearing thresholds were intact following surgery in the MFA and TMA groups. There was one case of profound postoperative deafness in the RWR group. Conclusion: MFA and TMA are both safe and effective techniques in the treatment of disabling SSCD. Since MFA is the more invasive technique, we suggest that TMA should be proposed as first‐line treatment, temporal bone anatomy permitting. RWR outcomes are more variable in term of symptomatic control, and this option could be offered to patients at risk under general anesthesia. L evel of evidence: Level 4 evidence.